Gambaran Cognitive Appraisal Anggota Kepolisian Satuan Reserse dan Kriminal (Satreskrim) Terhadap Tugas Rutin - Pradika Kurniawan; Nurlaela Widyarini; Istiqomah (Jurnal Psikologi, 2023)
Satreskrim members are responsible for maintaining security, enforcing the law, providing protection and services to the community. Routine duties involve interacting with the public, handling emergency situations, and enforcing the law. A study conducted by Danzler & McCoy (2006) shows that police officers must have the right characteristics to carry out their duties, this includes cognitive abilities, emotional abilities, motivation and attitudes towards the members' work. However, complex tasks and high demands put emotional pressure on police officers, so they need to carry out cognitive appraisals to cope with routine daily tasks. This research aims to describe the cognitive appraisal of members of the Police Criminal Investigation Unit (Sa-treskrim) regarding the routine tasks they carry out. The research uses descriptive quantitative methods. The sample consisted of members of the Criminal Investigation Unit at the Jember and Bondowoso Police Station in total (92 samples). Data was collected via Google form using the Cognitive Appraisals Questionnaire (CAQ) scale with 24 items with a Reliability value = 0.967. The results of the analysis show that the cognitive appraisal of Satreskrim members is generally in the high category, with an empirical mean of 96 which is greater than the hypothetical mean of 72. This means that Satreskrim has a high level of cognitive appraisal of routine tasks. This indicates that Satreskrim members have a positive cognitive assessment of the significance of routine tasks, consider routine tasks as something important, meaningful and believe that members have sufficient abilities and resources to carry out routine tasks, so that this can have implications for their motivation and performance in carry out daily tasks.